2022
DOI: 10.3389/fnut.2022.843357
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian Diet Was Associated With a Lower Risk of Chronic Kidney Disease in Diabetic Patients

Abstract: IntroductionDiabetes mellitus (DM) is a pathological hyperglycemic state related to the dysregulation of insulin. Chronic kidney disease (CKD) is a common chronic complication in diabetic patients. A vegetarian diet could be one of the preventive strategies for the occurrence of CKD in patients with diabetes mellitus. However, it is still unknown whether a vegetarian diet lowers the occurrence of CKD in DM patients.Research Design and MethodsThis retrospective study was conducted at Taipei Tzu Chi Hospital fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…Similar to our study, Szeto et al found that vegetarians had lower uric acid concentrations than omnivores [ 12 ]. In addition, few studies have reported that lacto-ovo vegetarians have lower risks of hyperuricemia or gout [ 11 , 15 ]. Unlike our previous study [ 15 ], a lacto-ovo vegetarian diet was not significantly linked to lower ORs for very high serum uric acid levels and CKD in patients with hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to our study, Szeto et al found that vegetarians had lower uric acid concentrations than omnivores [ 12 ]. In addition, few studies have reported that lacto-ovo vegetarians have lower risks of hyperuricemia or gout [ 11 , 15 ]. Unlike our previous study [ 15 ], a lacto-ovo vegetarian diet was not significantly linked to lower ORs for very high serum uric acid levels and CKD in patients with hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects completed structured dietary questionnaires [ 15 , 16 , 17 ] and underwent a comprehensive health examination. The dietary questionnaire on dietary practices in terms of type and duration as well as a quantitative food frequency questionnaire has been validated in previous studies [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the patients with diagnosed T2DM there is an even lower risk of CKD occurrence (OR: 0.68, 95% (CI): 0.57-0.82) for the lactoovo vegetarians and (OR 0.68, 95% CI: 0.49-0.94) for the vegan group (30). Moreover the control group tend to have more frequent incidence of proteinuria (27.7 vs 21.7% comparing to vegans and 20.5% in lacto-ovo vegetarian group, p < 0.001) (30) There is a signi cant difference between the lacto-ovo-vegetarian diet (VD) and Mediterranean diet (MD) with the mean difference of 4.2 mL/min/1.73 m² (p < 0.001) There is an 3.4 mL/min/1.73 m² increase between the initial and nal eGFR in a VD group. (Table 3).…”
Section: The Effect Of Vegetarian Diet On Ckd Parametersmentioning
confidence: 99%